RELATION BETWEEN TASTE AND NUTRITIONAL ADEQUACY WITH IMMUNITY OF ADOLESCENT IN BETHEL SENIOR HIGH SCHOOL DORMITORY IN BANJARBARU - Vivi Indria Wulandari; Rijanti Abdurrachim (Jurnal Riset Pangan dan Gizi, 2019)
Background: Lack of nutrition in adolescent can caused the decreasing of immunity towards disease, increasing the rate of disease, experiencing abnormal growth, low intelligence level and low productivity. Objectives: is to determine the relation between taste and nutritional adequacy with immunity of adolescent in Bethel Senior High School Dormitory in Banjarbaru. Method: This was an observational analytic research with cross sectional design. The population of this research is taken by saturation sampling which was all the students in first and second grade who live in Bethel Senior High School Dormitory in Banjarbaru with total amount was 49 people. The data retrieval was using questionnaire and 24 hour food recall form. This research was using Rank Spearman Correlation to analyse the data with 95% confidence interval.Results: The result of this research showed that there was 44,9% subjects who have low immune, 57,1% who have low taste perception, 46,9% who have low adequacy of energy, 49% who have low adequacy of protein, 51% who have low adequacy of fat, and 47,1% who have low adequacy of carbohydrate. The statistics data showed that there were relation between taste (p = 0,000 ; r = 0,887) and immune of adolescent, adequacy of energy (p = 0,000 ; r = 0,574) with immunity of adolescent, adequacy of protein (p = 0,000 ; r = 0,512) with immunity of adolescent, adequacy of fat (p = 0,000 ; r = 0,551) with immunity of adolescent, adequacy of carbohydrate (p = 0,000 ; r = 0,539) with immunity of adolescent . Both relation between dependent with 2 independent variables had strong bond to each other. Suggestion: The researcher suggests the employees of Bethel Senior High School Dormitory to increase the knowledge of food service so that it can increase the level of nutrition adequacy and respondent’s immune. Keywords : Taste, Nutrition Adequacy, Immunity